Motivation and Organizational Commitment on Loyalty and Islamic Banking Employee Performance - Zulkifli, Zulkifli; Hamzah, Hamzah; Hamzah, Zulfadli; Arif, Muhammad; Hamsal, Hamsal; Arsad, Syahiza (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2024)
Purpose: The purpose of this study was to determine the effect of motivation and organizational commitment on the loyalty and performance of Islamic bank employees, either directly or through mediating variables.Design/methodology: This research belongs to quantitative research with data analysis methods using Smart PLS 3.0 software. The research instrument used was a research questionnaire. The total sample of 353 employees.Findings: The results of the study found that Organizational Commitment affects Employee Performance, Organizational Commitment affects Loyalty, Loyalty affects Employee Performance, motivation has no effect on Employee Performance, motivation has no effect on loyalty, loyalty mediates the effect of organizational commitment on employee performance, but loyalty does not mediate the effect of motivation on employee performance. Practical implications: The Empirical implication of this research is to determine the conditions and factors that can increase of Islamic Bank Employee performance through motivation, organizational commitment, and loyalty.Originality/Value: This study recommend that Islamic banks should create activities or programs in the form of training or workshops or other activities to increase the spirit of employee motivation at work so that later it can lead to employee loyalty.Keywords: Motivation, Organizational Commitment, Loyalty, Employee Performance